Penerapan Framework for the Application of System Technique pada Penjualan Stationery Berbasis Website - Rima Tamara Aldisa (STMIK Budi Darma, 2022)
Stationery is an office stationery such as pencils, pens, books, paper, rulers, envelopes and many more in stock. Stationery shop sells various kinds of stationery. At this time, the way to market goods is still through opening a rented shop, using brochures and shop front banners. The occurrence of the problem is that the stationery shop owner has difficulty and has not been able to control the number of goods, sales data, both income and expenses. Designing a stationary sales system and developing it using the FAST (Framework for the Application of System Technique) method. The purpose of the research is that Aldi Stationery can have a website that is easy for buyers to use, attractive, can make it easier for shop owners to market goods, provide discounts and can also make it easier to manage and report sales transactions